Picture archiving and communication system—Asynchronous transfer mode network in a midsized hospital - Verma, Ramesh C. (Springer-Verlag, 1997)
This article describes the pathway to full implementation of a hospital information system-picture archiving and communication system-wide area network (HIS-PACS-WAN) in a 300-bed acute care hospital, and the linking of that system to two other off-site medical centers. The PACS included direct digital capture of computed tomography (CT), magnetic resonance (MR) imaging, nuclear medicine, and ultrasonography images into an Olicon archive. Plain radiographs and fluoroscopy images were digitized manually and archived into an Olicon system. The active archive included current images on each Olicon workstation and the juke box. Long-term archiving of the images on removable optical discs, which would be loaded manually by an operator every time a request for one of these studies appeared on the operator’s monitor, also was implemented. Ability to store, retrieve, and display simultaneously the physician’s report of each procedure along with the images was an ultimate goal. The WAN is to be used for teleradiology and teleconferencing among the three medical centers involved in this study as well as other off-site locations. Phase I included the design and installation of the local area network (LAN) in the Department of Radiology at Olive View-UCLA Medical Center. This included the clinics and the inpatient and hospitalwide fiber-optic network and its linkage to the local telephone company. Phase II involved linkage of the Olicon workstations to imaging equipment. This implementation has been delayed significantly because of inadequate needs assessment, absence of planning for forward-compatibility to imaging equipment, and incompatibilities in DICOM conformance among vendors. Every PACS project must include an in-depth needs analysis, which should be updated yearly because of rapid turnover of technology. Although this analysis should have a heavy emphasis on clinical needs, it must incorporate the hospital-wide needs for an integrated information systems network. Integration of PACS, HIS, RIS, and a dictation/transcription system is a complex task that requires a full-time, clinically oriented project officer for successful completion.